Ocena sevalne obremenjenosti ljudi pri nas in v svetu - Črnivec, Rajko (Medicinski razgledi, 2000)
The annual and cumulative radiation exposure of the non-professional Slovene population is 21% greater than that world-wide, and so is the risk of stochastic effects. During a lifetime of 70 years, there exists a statistically significant correlation between the effective radiation dose andcarcinogenicity for both the Slovene and world populations. Normal operation of nuclear power plants in Slovenia and in the world during their operational life does not cause tatistically significant stochastic effects onthe local population living nearby. Therefore, this should not be the main reason for premature nuclear power plant closures. A comparison of world-wide data on radiation exposure and the risk of stochastic effects for local populataon shows that the Krško nuclear power plant is at the same mean level.The stochastic effects on the population during their residence in the vicinity of the Žirovski vrh uranium mine, are statistically insignificant, but not excluded. According to legislation in force regarding radiation protection, it is necessary to monitor and register the radiation doses of medical origin in the population, in special cards enclosed with the health card. In professionally exposed persons, professional and non-professional radiation doses should be registered separately. The results of individual dosimetry should be registered properly and separately. Individual dosimetry should be supplemented to enable the calculation of effective radiation doses.A computerized state registry of radiation sources should be establishedin the Republic of Slovenia for professionally and non-professionally irradiated people in order to enable individual and epidemiological follow-up of their health risks.
Keywords: Radiation monitoring; sevanje; Environmental exposure; radiacija; Radiation, ionizing; škodljivost; učinki; Occupational exposure; Radiation effects; Slovenia; Slovenija; Radiation dosage; Nuclear reactors